If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 8 = -18 Reorder the terms: 8 + 3x = -18 Solving 8 + 3x = -18 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -8 + 3x = -18 + -8 Combine like terms: 8 + -8 = 0 0 + 3x = -18 + -8 3x = -18 + -8 Combine like terms: -18 + -8 = -26 3x = -26 Divide each side by '3'. x = -8.666666667 Simplifying x = -8.666666667
| 91-t=47 | | 28=e-12 | | 6s+19=109 | | 55=95-z | | 165-x=182 | | 5/6(18c-12)=20 | | 33=q-10 | | x^4-4x^3+2x^2-4x+40=0 | | 64-j=62 | | 165-x=185 | | 12n/2=18 | | 9=86-v | | 36=r-60 | | t-13=12 | | q-19=10 | | x-15=64 | | 21=g-42 | | 3(c+11)=45whatisc | | 16=b-74 | | 24=61-h | | 88-w=11 | | 7(b+2)=49whatisb | | 18x^2+51x+21=0 | | 42=e-7 | | 9-3k=17-k | | -6-(-9)/3 | | 84/280= | | (2x+4)dx+(3y-1)dy=0 | | 16w=7w+27 | | (2/5x)(5y)(-2x)= | | 2.5-y= | | y=(5-3x)/(7-4x) |